2019
DOI: 10.3389/fpsyg.2019.01529
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Emotional Intelligence as Protective Resources for Well-Being in Moroccan Adolescents

Abstract: This study aimed to test a structural model to examine the protective role of psychosocial variables, such as social support, emotional intelligence and their interaction, on the cognitive dimension of subjective positive well-being (life satisfaction) and negative well-being (depression) in Moroccan adolescents. The participants consisted of 1277 students (571 men, 694 women and 12 missing values) with a mean age of 16.15 years ( SD = 2.22; range = 9 to 23) who attended 26 public school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 102 publications
6
36
0
9
Order By: Relevance
“…This result supports the importance of intervention programs for adolescents with clear implications for educational practice. Finally, other studies finding that EI and social support prevent depression (Lopez-Zafra et al, 2019) are extended by our finding that this effect also influences self-concept by reducing the negative impact of depression, thus supporting H4. This result in Moroccan students is in line with results in other countries reported by MacCann et al (2020) in which indicate that the contribution of EI in the regulation of negative emotions (i.e., anxiety or boredom) is responsible of the positive effects of EI on academic performance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result supports the importance of intervention programs for adolescents with clear implications for educational practice. Finally, other studies finding that EI and social support prevent depression (Lopez-Zafra et al, 2019) are extended by our finding that this effect also influences self-concept by reducing the negative impact of depression, thus supporting H4. This result in Moroccan students is in line with results in other countries reported by MacCann et al (2020) in which indicate that the contribution of EI in the regulation of negative emotions (i.e., anxiety or boredom) is responsible of the positive effects of EI on academic performance.…”
Section: Discussionsupporting
confidence: 87%
“…Our starting point is the study by Lopez-Zafra et al (2019), in which the authors prove that social support and EI are protective factors for well-being, positively increasing life satisfaction and reducing depression. Here, we further test whether socioemotional adjustment relates to academic adjustment in Moroccan adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is widely acknowledged that individuals with high levels of emotional intelligence, measured as a trait and as an ability, report higher life satisfaction. [20][21][22][23][24][25] Some other studies confirm that emotional intelligence is a significant predictor of hedonic and eudemonic well-being. 26,27 The meta-analysis conducted by Sánchez-Álvarez and colleagues 28 on a total of 25 studies and on a combined sample of more than 8000 participants provides evidence of a significant positive relationship between emotional intelligence and life satisfaction (r = 0.32).…”
Section: Introductionmentioning
confidence: 90%
“…Previous research has shown that EC/EI are associated with positive wellbeing outcomes [ 25 , 26 ], including mediating wellbeing outcomes [ 27 ]. This study adds to the literature by further exploring the development of emotional literacy (as a component of WL) via a brief online PPI.…”
Section: Introductionmentioning
confidence: 99%